2018
DOI: 10.5194/aab-61-459-2018
|View full text |Cite
|
Sign up to set email alerts
|

The effects of natural mating and artificial insemination using cryopreserved buck semen on reproductive performance in Alpine goats

Abstract: This study compared the effects of natural mating and artificial insemination using frozen buck semen on reproductive performance in Alpine goats. Sixty reproductive Alpine goats were grouped according to natural mating (n = 30) and artificial insemination (n = 30) breeding methods. Oestrus was synchronised in experimental goats using a vaginal sponge impregnated with 20 mg of progestogen FGA (fluorogestone acetate) for 11 days. At the time of sponge insertion, 150 µg of prostaglandin F 2α (PGF 2α ) analogue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Ở trên heo, quá trình thủy tinh hóa giảm rõ rệt khả năng vận động, khả năng tồn tại và tính toàn vẹn acrosome của tinh trùng (Arraztoa et al, 2017;My và ctv., 2021). Kết quả giảm chất lượng tinh trùng sau khi giải đông cũng có kết quả tương tự, hiệu quả thấp hơn so với phương pháp đông lạnh chậm cũng ở cừu, dê, gia cầm ( Long et al, 2010);Jiménez-Rabadán et al, 2015;Agossou & Koluman, 2018).…”
Section: Phương Pháp Thủy Tinh Hóaunclassified
“…Ở trên heo, quá trình thủy tinh hóa giảm rõ rệt khả năng vận động, khả năng tồn tại và tính toàn vẹn acrosome của tinh trùng (Arraztoa et al, 2017;My và ctv., 2021). Kết quả giảm chất lượng tinh trùng sau khi giải đông cũng có kết quả tương tự, hiệu quả thấp hơn so với phương pháp đông lạnh chậm cũng ở cừu, dê, gia cầm ( Long et al, 2010);Jiménez-Rabadán et al, 2015;Agossou & Koluman, 2018).…”
Section: Phương Pháp Thủy Tinh Hóaunclassified
“…Goat reproduction is affected by seasonality, where the normal breeding season occurs when days are shorter, followed by a period of anestrous, and consequently, a decline in reproduction is observed when days are longer (Fatet et al, 2011); therefore, seasonality is considered as a major limiting factor. It has shown that pregnancy rate was higher during high‐breeding season compared with low‐breeding season (LBS), and this leads to a continuous struggle to optimize strategies for the improved reproduction during LBS in goats (Agossou & Koluman, 2018). In the past, administration of exogenous melatonin along with the presence of males resumed the reproductive performance during LBS; however, it negatively affected the resumption of ovarian activity during the breeding season (Zarazaga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Semen cryopreservation is a routine practice in goats, followed by artificial insemination (AI), and it is regarded as a vital approach for establishing the genetic resource bank (Lv et al, 2019). Yet, it offers great challenges for achieving high‐quality sperm viability and subsequently its reproductive performance (Agossou & Koluman, 2018), so differnt cryopreservation protocols have been investigated in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it offers great challenges for achieving high-quality sperm viability and subsequently its reproductive performance (Agossou & Koluman, 2018), so differnt cryopreservation protocols have been investigated in this context.…”
Section: Introductionmentioning
confidence: 99%